3D-printed bolus ensures the precise postmastectomy chest wall radiation therapy for breast cancer - Wang, Xiran; Zhao, Jianling; Xiang, Zhongzheng; Wang, Xuetao; Zeng, Yuanyuan; Luo, Ting; Yan, Xi; Zhang, Zhuang; Wang, Feng; Liu, Lei (Frontiers in Oncology, 2022)
Purpose To investigate the values of a 3D-printed bolus ensuring the precise postmastectomy chest wall radiation therapy for breast cancer. Methods and materials In the preclinical study on the anthropomorphic phantom, the 3D-printed bolus was used for dosimetry and fitness evaluation. The dosimetric parameters of planning target volume (PTV) were assessed, including Dmin, Dmax, Dmean, D95%, homogeneity index (HI), conformity index (CI), and organs at risk (OARs). The absolute percentage differences (|%diff|) between the theory and fact skin dose were also estimated, and the follow-up was conducted for potential skin side effects. Results In preclinical studies, a 3D-printed bolus can better ensure the radiation coverage of PTV (HI 0.05, CI 99.91%), the dose accuracy (|%diff| 0.99%), and skin fitness (mean air gap 1.01 mm). Of the 27 eligible patients, we evaluated the radiation dose parameter (median(min–max): Dmin 4967(4789–5099) cGy, Dmax 5447(5369–5589) cGy, Dmean 5236(5171–5323) cGy, D95% 5053(4936–5156) cGy, HI 0.07 (0.06–0.17), and CI 99.94% (97.41%–100%)) and assessed the dose of OARs (ipsilateral lung: Dmean 1341(1208–1385) cGy, V5 48.06%(39.75%–48.97%), V20 24.55%(21.58%–26.93%), V30 18.40%(15.96%–19.16%); heart: Dmean 339(138–640) cGy, V30 1.10%(0%–6.14%), V40 0.38%(0%–4.39%); spinal cord PRV: Dmax 639(389–898) cGy). The skin doses in vivo were Dtheory 208.85(203.16–212.53) cGy, Dfact 209.53(204.14–214.42) cGy, and |%diff| 1.77% (0.89–2.94%). Of the 360 patients enrolled in the skin side effect follow-up study (including the above 27 patients), grade 1 was the most common toxicity (321, 89.2%), some of which progressing to grade 2 or grade 3 (32, 8.9% or 7, 1.9%); the radiotherapy interruption rate was 1.1%. Conclusion A 3D-printed bolus can guarantee the precise radiation dose on skin surface, good fitness to skin, and controllable acute skin toxicity, which possesses a great clinical application value in postmastectomy chest call radiation therapy for breast cancer.